Tensile behaviour of spring steel wire reinforced EN AW-6082. (February 2015) - Merzkirch, Matthias; Meissner, Marius; Schulze, Volker; Weidenmann, Kay André
The reinforcement of composite aluminium extrusions offers a high potential regarding weight reduction and improvement of mechanical properties, which is essential for components in lightweight constructions. The current work gives an overview of the quasi-static properties of spring steel wire reinforced EN AW-6082 with varying reinforcing ratio. The deformation and damage behaviour is investigated in detail for a reinforcing ratio of 11.1 vol.%. It is shown that the relatively ductile behaviour of the spring steel wire leads to multiple necking resulting in higher strains than expected. Current models are expanded and modified for a proper adaptation to the material system.